The relationship between the loess stratigraphy in the Vojvodina region of northern Serbia and the Saalian and Rissian Stage glaciations – a review - Marković Slobodan B. (BOREAS, 2024)
The regional loess stratigraphy in the Vojvodina region, in the southeastern Carpathian Basin, has often been successfully correlated to the global palaeoclimate. This is a quasi-continuous sedimentary record that provides detailed environmental reconstruction during the last four glacial/interglacial cycles. In this study, we present a standardized loess stratigraphy and illustrate how it correlates with the marine oxygen isotope and Chinese loess stratigraphical records. We argue that the loess stratigraphy in Vojvodina region is an important link in the integration of European terrestrial stratigraphical schemes and the deep-sea stratigraphical model. We highlight how the loess record can better illustrate terrestrial environmental change through multiple glacial cycles than other records, such as glacial records. The investigated loess record enables direct links to be made between the loess sediments and their glacial sources. This reveals evidence of glaciations during every glacial cycle of the Saalian Stage complex, equivalent to Marine Isotope Stage (MIS) 10, 8 and 6. Therefore, Serbian loess has the potential to provide a direct link between terrestrial glaciations and wider records of global climate change, which is an enigma for many other continental records. These loess records display a strong relationship with the intensity of European glaciations during different glacial cycles. Loess sedimentation rates are highest in the most intensive European glaciation of the Saalian complex (MIS 6) and much lower during the weaker ?missing? glaciations equivalent to MIS 8 and 10. A key observation from the Vojvodina loess is the gradual increase in interglacial aridity through the late Middle Pleistocene. The explanation for the progressively increasing aridity in the investigated region at this time is still unclear. However, this trend is consistent with the idea of the Saalian complex as representing a 400?ka mega glacial cycle modulated by shorter classic 100?ka glacial cycles.